Resveratrol-procyanidin blend: nutraceutical and antiaging efficacy evaluated in a placebo-controlled, double-blind study - Buonocore D; Lazzeretti A; Tocabens P; Nobile V; Cestone E; Santin G; Bottone MG; Marzatico F (Dove Medical Press, 2012)
Daniela Buonocore,1 Angelo Lazzeretti,2 Pedro Tocabens,3 Vincenzo Nobile,4 Enza Cestone,4 Giada Santin,5 Maria G Bottone,5,6 Fulvio Marzatico11Laboratory of Pharmacobiochemistry, Nutrition and Nutraceutical of Wellness, Department of Biology and Biotechnology “L Spallanzani”, University of Pavia, Pavia, Italy; 2GMC Pharma SRL, Milan, Italy; 3Actafarma Laboratorios, Madrid, Spain; 4Farcoderm SRL European Network for Tests in Dermatology and Wellness, Pavia, 5Laboratory of Cell Biology and Neurobiology, Department of Biology and Biotechnology “L Spallanzani”, 6Institute of Molecular Biology CNR, Section of Histochemistry and Cytometry, University of Pavia, Pavia, ItalyBackground: Skin is constantly exposed to pro-oxidant environmental stress from several sources, including air pollutants, ultraviolet solar light, and chemical oxidants. Reactive oxygen species have been implicated in age-related skin disorders. Dietary bioactive antioxidant compounds, such as polyphenols, have beneficial effects on skin health. The advantage of a nutritional administration route is that blood delivers nutraceutical bioactive compounds continuously to all skin compartments, ie, the epidermis, dermis, and subcutaneous fat. The purpose of this study was to evaluate the topical and systemic effects of a dietary supplement containing resveratrol and procyanidin on age-related alterations to the skin, the skin antioxidant pool, and systemic oxidative stress levels.Methods: An instrumental study was performed in 50 subjects (25 treated with supplements and 25 with placebo) to identify clinical features induced by chronoaging or photoaging. Product efficacy was evaluated after 60 days of treatment in terms of in vivo and in situ skin hydration, elasticity, and skin roughness levels, systemic oxidative stress levels by plasmatic derivatives of reactive oxygen metabolites and oxyadsorbent tests, and extent of the skin antioxidant pool.Results: After 60 days of treatment, values for systemic oxidative stress, plasmatic antioxidant capacity, and skin antioxidant power had increased significantly. Additionally, skin moisturization and elasticity had improved, while skin roughness and depth of wrinkles had diminished. Intensity of age spots had significantly decreased, as evidenced by improvement in the individual typological angle.Conclusion: Nutraceutical and pharmacological intervention with a supplement characterized by a specific blend of resveratrol and procyanidin may be a promising strategy to support treatments for the reduction of skin wrinkling, as well as reducing systemic and skin oxidative stress.Keywords: antiaging, nutraceuticals, procyanidin, resveratrol supplementation, skin